The substance abuse handbook - Ruiz, Pedro; Strain, Eric C (Philadelphia : Wolters Kluwer Health, 2014)
"Stay up to date with the latest substance abuse treatments and modes of intervention with The Substance Abuse Handbook, 2e. The editors are both nationally recognized clinicians, and provide authoritative, clinically oriented information on the subject of substance use, abuse, and dependence, with an emphasis on diagnosis, treatment, and prevention.You'll find focused, expert information on every aspect of the field, including etiological factors; substances of abuse; compulsive and addictive behaviors; evaluation and diagnostic classification; treatment modalities, management of associated medical conditions; substance abuse in youth and the elderly; women's issue; special groups and settings; models of prevention; training and education; and policy issues. Succinctly presenting the most clinically relevant information from Lowinson and Ruiz's Substance Abuse, 5e, this concise, portable handbook is a must-have reference for anyone involved directly or indirectly in the addiction field.New to This Edition Find the practical information you need fast with this edition's focused coverage of basic science and greater emphasis on clinical concerns. Stay current with the latest information in the field, including changes reflecting the release of DSM-5. Access updated information in key topic areas, including "Special Populations," "Special Settings," and "Models of Prevention."--
"The second edition of The Substance Abuse Handbook will again follow the general organization of the 'big' book, Lowinson and Ruiz's Substance Abuse. This title distills content from the larger text into a concise, portable guide for healthcare professionals who need to diagnose and treat addictive disorders and related medical conditions"--Provided by publisher.
Companion to: Lowinson and Ruiz's substance abuse : a comprehensive textbook / editors, Pedro Ruiz, Eric C. Strain. 5th ed. c2011.
Includes bibliographical references and index.
Keywords: Substance-related disorders; Addictions; Substance abuse; Substance misuse